9
$\begingroup$

Today I have encounter a series:

$$\sum_{n=-\infty}^{+\infty}\frac{1}{(u+n)^2}=\frac{\pi^2}{(\sin \pi u)^2}$$ where $u \not \in \Bbb{Z}$ . I have known a method to computer it (by Residue formula): $$\int_{|z|=N+1/2}\frac{\pi \cot \pi z}{(u+z)^2}\text{dz}=-\frac{\pi^2}{\sin^2 \pi u}+\sum_{k=-N}^{N}\frac{1}{(u+k)^2}$$

where $-u$ is a pole of order 2. and $n \in \Bbb{Z}$ and $|n| \leq N$ are poles of order 1. because $$\left|\int \frac{\pi \cot \pi z}{(u+z)^2}\text{dz}\right|\leq \int_0^{2\pi}\pi\left|1+\frac{2}{e^{i2\pi z}-1}\right|\frac{1}{|((N+1/2)e^{i\varphi}+u)^2|}\text{d}\varphi \rightarrow 0$$ as $N \rightarrow +\infty$

Dose there exists some other way to computer it?

$\endgroup$
  • 2
    $\begingroup$ It is a direct application of Fourier transform and Poisson summation formula. See here for a related problem. $\endgroup$ – Mhenni Benghorbal Feb 26 '13 at 16:21
9
$\begingroup$

Consider the Weierstrass form of the Gamma function:

$$\frac{1}{\Gamma (x)}=xe^{\gamma x}\prod_{n\geq 1}\left(1+\frac{x}{n}\right)e^{-\frac{x}{n}}$$ Then:

$$\ln\Gamma (x)=-\ln x-\gamma x+\sum_{n\geq 1}\left[\frac{x}{n}-\ln \left(1+\frac{x}{n}\right)\right]$$

$$\frac{d}{dx}\ln\Gamma(x)=-\frac{1}{x}-\gamma+\sum_{n\geq 1}\left(\frac{1}{n}-\frac{1}{n+x}\right)$$

$$\begin{align*}\frac{d^2}{dx^2}\ln\Gamma (x)&=\frac{1}{x^2}+\sum_{n\geq 1}\frac{1}{(n+x)^2}\\[7pt]&=\sum_{n\geq 0}\frac{1}{(n+x)^2}\quad(1)\end{align*}$$

Note that by letting $x\to 1-x$ and $n\to-n-1$ we also have:

$$\frac{d^2}{dx^2}\ln\Gamma(1-x)=\sum_{n\leq -1}\frac{1}{(n+x)^2}\quad(2)$$

Combine $(1)$ and $(2):$

$$ \begin{align*}\sum_{\mathbb{Z}}\frac{1}{(n+x)^2}&=\frac{d^2}{dx^2}\ln\Gamma(1-x)+\frac{d^2}{dx^2}\ln\Gamma(x)\\&=\frac{d^2}{dx^2}\ln \Gamma(x)\Gamma(1-x)\\[7pt]&=\frac{d^2}{dx^2}\ln\pi\csc \pi x\quad(x\not\in\mathbb{Z})\\[7pt]&=\pi^2\csc^2\pi x\end{align*}$$

$\endgroup$
  • $\begingroup$ It is a very nice proof and I like it. This identity has lots of applications. $\endgroup$ – xpaul Apr 25 '13 at 20:48
3
$\begingroup$

Let $f(z) =\displaystyle \sum_{n\in \mathbb{Z}} \frac{1}{(n+z)^2}$ and $g(z) = \dfrac{\pi^2}{\sin^2(\pi z)}.$ Both functions are $1$ periodic, so it suffices to understand their behavior in the strip $\mathfrak{R}(z)\in [0,1).$ It is straightforward to verify that both these functions have a singularity only at the origin and are bounded on the strip excluding any neighborhood of the origin.

Now look near $z=0.$ We have $f(z) =\displaystyle \frac{1}{z^2} + \sum_{n\in\mathbb{Z}\setminus\{0\}} \frac{1}{(z+n)^2}.$ By the power series expansion of sine and geometric series, we have $$ g(z) = \frac{\pi^2}{\pi^2 z^2 - (\pi^4/3)z^4 + \mathcal{O}(z^6) } = \frac{1}{z^2} \left( \frac{1}{1- (\pi^4/3) z^2 + \mathcal{O}(z^4) } \right) = \frac{1}{z^2} \left( 1 + (\pi^2/3) z^2 + \mathcal{O}(z^4) \right) = \frac{1}{z^2} +\pi^2/3 + \mathcal{O}(z^2).$$

So in fact $f(z)-g(z)$ is bounded and analytic on the strip, and hence the whole complex plane. By Liouville's theorem, $f(z)-g(z) = f(0)-g(0)=0$ so $f(z) = g(z).$

$\endgroup$
  • $\begingroup$ Yes, this is the classical proof from Ahlfors. $\endgroup$ – Bombyx mori May 29 '14 at 7:46

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.